Training on the use of edmodo as a learning media - Rhaishudin Jafar Rumandan; Muhammad Kashai Ramdhani Pelupessy (Balai Diklat Keagamaan Ambon, 2023)
The purpose of this training is to train teachers to use the online learning media platform Edmodo to make it easier for teachers to learn. The method used in this training was training and workshops. The participants in this training were teachers of SMP Negeri 3 Huamual, West Seram Regency, totaling 30 people, with a male percentage of 36% and a female of 64%. The steps in conducting the training are as follows: Conducting a survey at Huamual 3 Public Middle School, West Seram Regency, and identifying the problems faced by schools related to distance learning. (1) We analyze the needs of schools for widely used E-learning platforms. (2) Conduct a literature study on the use of the Edmodo application. (3) Prepare training support tools and materials. (4) Determine and prepare the material to be delivered. Training on the use of Edmodo Media in the learning process went well and smoothly. The results of this activity are: After this training, teachers will acquire new knowledge and skills in using the Edmodo-based learning environment in the teaching and learning process. The results of the evaluation through observation during training using Edmodo, the teacher was very enthusiastic, this was seen during the question and answer during the work practice.